Упростите выражение: ( 5x^2y+x^4−4y)+(−2y+2x^4 + 8 x^2y)

0 голосов
33 просмотров

Упростите выражение: ( 5x^2y+x^4−4y)+(−2y+2x^4 + 8 x^2y)


Алгебра (96 баллов) | 33 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:


(5 {x}^{2} y + {x}^{4} - 4y) + ( - 2y + 2 {x}^{4} + 8 {x}^{2} y) = \\ = (5 {x}^{2} y + 8 {x}^{2} y) + ( {x}^{4} + 2 {x}^{4} ) + ( - 4y - 2y) = \\ = 13 {x}^{2} y + 3 {x}^{4} - 6y \\ \\



(25.7k баллов)
0 голосов

( 5x^2y+x^4−4y)+(−2y+2x^4 + 8 x^2y) =

5x^2y + x^4 - 4y - 2y + 2x^4 + 8x^2y =

5x^2y + 8x^2y + x^4 + 2x^4 - 4y - 2y =

        13x^2y  +  3x^4  - 6y

(2.1k баллов)